The Cheapest Way to Europe: Illegal Migration and Women Objectification in African Film - Ogundipe, Stephen Toyin; Ayoade, Rachael Fisayo (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This paper explores the dynamics of irregular migration and the objectification of women in Boris Lojkine’s film Hope, highlighting the increasing prominence of these themes in African films. Through an analysis grounded in Martha Nussbaum’s feminist perspectives on objectification, the article examines how the film director portrays the female body as a commodity. The paper posits that sexual objectification is a gendered phenomenon and that the objectified body is almost always the female body. The findings reveal a gendered survival strategy employed by migrants facing insurmountable challenges in their attempts to leave Africa. It concludes that the commodification of female migrants becomes an unavoidable consequence for those who successfully navigate the dangerous and unlawful routes to Europe.